Mucoactive therapy in community-acquired pneumonia - Andrey A. Zaytsev; Ekaterina A. Filon (ZAO "Consilium Medicum", 2023)
Aim. To study the clinical efficacy of Bronchipret syrup compared with the standard (real-world practice) mucoactive therapy for patients with viral pneumonia. Materials and methods. The observation study included patients 1870 years old who presented with productive cough and were admitted to the pulmonology department with medically confirmed community-acquired pneumonia (CAP). The study included 60 patients; Group 1 included 30 patients who received Bronchipret syrup 5.4 mL 3 times a day for up to 1014 days. The other 30 patients with CAP were included in Group 2 (control), in which other mucoactive drugs were used at the discretion of the physician: acetylcysteine in 56.7% of patients, ambroxol in 30%, and bromhexine in 13.3%. The duration of therapy was established by a physician for a period of 1014 days. Results. A significant decrease in sputum secretion was observed during treatment with Bronchipret (Group 1) on average on day 4 (after 4.31.2 days) and after 4.50.9 days in group 2. A decrease in the severity of daytime cough in Group 1 was observed after 4.91.2 days vs. 5.11.1 days in Group 2. The nocturnal cough stopped in 2.71.3 days in Group 1 and 2.60.9 days in Group 2. Conclusion. The data support the use of combined products containing ivy and thyme in patients with CAP and mucolytics.